LEVEL CROSSING SAFETY IN THE CZECH REPUBLIC - Martin Kobosil; Jan Novák (Acta Polytechnica CTU Proceedings)
This paper describes safety threats at level crossings according to the different type of security equipment. Initially were explored statistical data, which consist of numbers of level crossings classified by crossing type and numbers of traffic accidents on level crossings. Afterwards paper describes specific problems of each individual level crossing type. Specifically their causation and consequences, which are being discussed between professional and general public. In conclusion paper describes possible solutions to these problems leading to reducing risks at level crossings. At first is mentioned the statistics - number of crossing and number of accidents on the crossing. Then paper describes specific problems, which are discussed in professional and general public. They are also solutions of this problems, which brings another point of view and search the actual causes.